QLTI-16. ENHANCED RECOVERY AFTER LASER ABLATION SURGERY: A PRELIMINARY ANALYSIS OF A NOVEL PROGRAM. (14th November 2022) - Merenzon, Martin; Levy, Adam; Eatz, Tiffany; Morell, Alexis; Higgins, Dominique; Patel, Nitesh; Kader, Michael; Eichberg, Daniel; Shah, Ashish; Silva, Michael; Lu, Victor; Luther, Evan; et al.
Abstract: INTRODUCTION: The concept of enhanced recovery after surgery (ERAS) due to standardized interventions has been gaining more relevance within neurosurgery. Advances were made both in protocols for spine and cranial surgery. These experiences described many benefits such as less psychological stress, reduction in hospitalization days, and lower hospital costs, without increasing the incidence of complications. However, no experience has described to date the applicability of an ERAS program for laser ablation thermal therapy (LITT). OBJECTIVE: To describe our initial experience with the first enhanced recovery program reported for laser ablation for brain tumors. Secondly, to summarize the perioperative clinical outcomes of ERAS applied to LITT. METHODS: We performed a retrospective analysis of all adult patients who underwent LITT for oncological lesions from 2013 to 2021. A multidisciplinary program was created by protocolizing interventions carried out along the path of the patient's hospitalization. Each recommendation was individually assessed for its appropriateness for enhancing recovery and for its validity with a focused literature review process. RESULTS: A total of 184 patients were included, with a mean age of 60.7 ± 13.5 years, 35% males. 167 tumors were located in the supratentorial compartment, and 17 were infratentorial; the mean tumor diameter was 1.84 ± 1.04 cm. Among the pathologies treated 50.0% were metastasis, and 36.9% were glioblastomas. The mean postoperative day discharge was 1.2 ± 0.8 days. The readmission rate due to surgical complications within 30 days of surgery was 2.7%. These readmission rates fall into what is expected according to published literature without an ERAS program and longer hospital admissions. One death was recorded in the perioperative period. CONCLUSION: Clinical interventions that could constitute an ERAS program are feasible in laser ablation of brain tumors. This study could be useful as a preliminary framework for the development of future guidelines.